"Girls like Girls" A study on the level of Homosexuality and Behavioral Responses among selected young females. - Corto, Rose Ann D., et al; Cubilla, Reyna C.; Septimo, Cere Ann E. (Rose Ann Corto, 2011)
This study aims to determine the commonality of occurrence of same-sex attraction among young females, the intensity of the attraction, the ways of acceptance, the control of emotion, and the ways of coping of females who are the subjects of this study. The study includes 140 research respondents who answered a 30-item questionnaire followed by in-depth interviews with 15 selected subjects. The researchers were able to come up with the following results: 47.86% of the total respondents (140) have felt sexually attracted towards their same sex; among the 15 respondents who were interviewed for the in depth discussion, (93%) did not find it hard to accept their homosexual feelings. In the Chi-Square Test of Significant Difference between the responses of moderate and high intensity level of attraction of the respondents and the response of whether pursuing in courtship to gratify their attraction, Ho is rejected when there is no significant difference of the respondents' responses. The most appropriate response that the respondents do when they feel attracted to their same sex is they usually court. The respondents' ways of controlling or coping with their homosexual feelings towards the same sex especially when rejected are: refraining from communicating with the person through keeping themselves busy in school or at work; others chose to divert their attention to other person; have resorted to drinking with their friends; and other activities such as listening to music and playing games or sports to forget the person. Recommendation for future researches suggests the it is always advisable to eliminate the biases towards the subjects because this will in turn lead to biased results and the credibility and reliability of such results will also be questioned.